1995
DOI: 10.2355/isijinternational.35.1006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hot Deformation on Bainite Structure in Low Carbon Steels.

Abstract: Hyogo-ken, 660 Japan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…It is reasonable to assume that densely stacked dislocation arrays introduced intragranularly by austenite deformation can act as nucleation sites for AF. Actually, the nucleation of AF has been found at various deformation substructures, like deformation bands [9,13,56,57] and dislocation cell walls [58]. Therefore, despite a wide range of cooling rates used (5-50°C s -1 ) in this research, for samples undeformed (strain2 = 0) or slightly deformed (strain2 = 0.1), laths nucleated primarily on PAGBs where densely stacked dislocation arrays can be accommodated, and these laths finally developed into BF packets with a parallel morphology as shown in Figs.…”
Section: Transition From Bf To Afmentioning
confidence: 99%
“…It is reasonable to assume that densely stacked dislocation arrays introduced intragranularly by austenite deformation can act as nucleation sites for AF. Actually, the nucleation of AF has been found at various deformation substructures, like deformation bands [9,13,56,57] and dislocation cell walls [58]. Therefore, despite a wide range of cooling rates used (5-50°C s -1 ) in this research, for samples undeformed (strain2 = 0) or slightly deformed (strain2 = 0.1), laths nucleated primarily on PAGBs where densely stacked dislocation arrays can be accommodated, and these laths finally developed into BF packets with a parallel morphology as shown in Figs.…”
Section: Transition From Bf To Afmentioning
confidence: 99%
“…Actually, the nucleation of AF has been observed on many deformation defects, such as deformation bands [18,[44][45][46] and dislocation cell walls. [47] C.…”
Section: B Transition From Bf To Afmentioning
confidence: 99%
“…Yamamoto et al [11] and Yang et al [10] suggested that AF nucleates on deformation bands, and Yakubtsov and Boyd [14] indicated that dislocations are the intragranular nucleation sites. The preceding articles [9][10][11]14] report observations for conditions where deformed austenite is a prerequisite for AF formation. By contrast, Lee et al [15] have studied the effects of austenite deformation on AF formation, under conditions where AF is the predominant transformation product in undeformed austenite.…”
Section: Introductionmentioning
confidence: 94%
“…Fujiwara et al [9] showed that AF forms in deformed austenite during isothermal transformation and that the transformation rate is higher for AF than for CB. It was also shown that the AF lath length decreases with increasing austenite deformation strain below T NR , and it was suggested that AF nucleates on dislocation cell (DC) walls.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation